COMPARISON OF GLOMERULAR FILTRATION RATE AND CHRONIC KIDNEY DISEASE PREVALENCE USING COCKCROFT-GAULT(C-G) AND MODIFICATION OF DIET IN RENAL DISEASE (MDRD FOR CHINESE FORMULA AMONG BALINESE POPULATION - Widiana, I Gde Raka; Suwitra, Ketut (Medicina, 2015)
Some community based study to determine the prevalence of chronic kidney disease has been conducted.It is reported that a reasonable rate of prevalence of CKD if calculated with different formula (either C-Gor MDRD). This  study  is aiming  to  compare estimated GFR and CKD prevalence determined byeitherC-G or MDRD  and the new Chinese modified MDRD formulaThis  study  analyzed  4528  subjects  from  7  areas  in Bali  Islands  including  219(4.8%)    subjects  inSembiran, 302 (6.7%), Denpasar 302 (6.7%), Nusa Ceningan 305 (6.7%), Legian282 (6.2%)  Blahbatuh3038(67.1%), Tenganan,  81(1.8%),  and  in Ubud  301(6.6%),  consisted  2217  (49%) males  and  2311(51%) females. It is found that there were a substantial differences and stepwise increase (79, 83, 86,and105 mL/min/  1.73 m2),  consecutively  of mean  of  estimated-GFR  if  calculated  by C-G, MDRD,MDRD for Chinese (if  non-Chinese), and MDRD for Chinese (if Chinese) formula. It was also foundthat differences of prevalence rate CKD using different formulas.  More than twenty percent (20.6%) ofCKD defined by estimated-GFR of 59 to 30 ml/min per 1.73m2 when were calculated by C-G,  and 6.9and 6.8 percent if were calculated by MDRD and  MDRD for Chinese (if  non-Chinese), consecutively,however, it is much lower (2.2%) using MDRD formula for Chinese (if Chinese).In conclusion, this study shows difference inmeanvalues of e GFR and  prevalence of CKD if calculatedusing  different  formulas. A  valid  formula  is  needed  for  specific  Indonesian  people.  [MEDICINA2014;45:151-155].
Keywords: estimated glomerular filtration rate - Cockcroft-Gault - Modification of Diet in Renal Disease ? Chinese population ? Indonesian population